Participatory Forestry: Involvement, Information and Science - Paletto, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Public participation in forestry is a key issue in ensuring the democratization of decision-making processes, increasing the social acceptance of policies, and reducing conflicts between forest users. Public participation also provides an opportunity for the improvement of the quality of information, public debate, personal reflection, and professionalization, raising awareness. Participation in forestry implies the involvement of stakeholders (the interest group participation approach) and/or the involvement of people (the direct citizen participation approach) in the decision-making process. Since the UN Conference on Environment and Development (1992), new norms and perspectives have emerged encouraging a bottom-up approach in forest governance. Consequently, several participatory techniques, methods, and tools for stakeholder involvement in forest governance have been developed and applied. These different experiences allow us to learn from failures and successes and contribute to knowledge improvement. The future challenges of participatory forestry deal with adaptation to changes in ecological, social, and economic contexts.